The Interpersonal Effects of Emotions in Negotiations A Motivated Information Processing Approach. (article). - Van Kleef, Gerben A.
Three experiments tested a motivated information processing account of the interpersonal effects of anger and happiness in negotiations . In experiment 1, participants received information about the opponent's emotion (anger, happiness and none) in a computer-mediated negotiation, As predicted, they conceded more to an angry opponent than to an happy one )controls falling in between), but onlly when they had a low (rather than a high) need for cognitive closure. Experiment 2 similarly showed that participants were only affected by the others emotion under low rather high time pressure reduced their degree of information processing. Finally, Experiment 3 showed that negotiations were only influenced by their opponent's if they had low (rather than high) power. These results support the motivated information processing model by showing that negotiations are only affected by their opponent's emotions if they are motivated to consider them. -- (from the author)